A Case of Fulminant Listeria Rhombencephalitis with Brainstem Abscesses in a 37-Year-Old Immunocompetent Patient: From Vestibular Neuritis to Ondine's Curse - Percuoco, Veronica; Kemp, Oliver; Bolognese, Manuel; von Hessling, Alexander; Scholte, Johannes B.J.; Schneider, Ulf C. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
We present a rare case of Listeria monocytogenes (LM) rhombencephalitis with the formation of multifocal abscesses in a young immunocompetent patient. His initial symptoms of dizziness, headache, and feeling generally unwell were put down to a coincidental coinfection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The unfortunate rapid progression to trigeminal, hypoglossal, vagal, facial, and abducens nuclei palsies, and then an acquired central hypoventilation syndrome, known as Ondine's curse, required a prolonged intensive care unit (ICU) stay, and prolonged mechanical ventilation. As they continued to deteriorate despite targeted antibiotic treatment, surgical drainage of the abscesses was seen as the only meaningful available treatment option left to contain the disease. Postoperatively, the patient's strength rapidly improved as well as the severity of the cranial nerve palsies. After prolonged rehabilitation, at 3 months of follow-up, the patient was weaned off mechanical ventilation, independently mobile, and was left with only minor residual neurologic deficits. This case highlights a number of interesting findings only touched upon in current literature including the route of entry of LM into the central nervous system, the rare entity of acquired central hypoventilation syndrome, and finally the use of surgical intervention in cerebral LM infections.
Keywords: Listeria monocytogenes; brainstem abscess; rhombencephalitis